ANALISIS KADAR ASAM URAT PADA LANSIA DI WILAYAH KERJA PUSKESMAS AIR SUGIHAN KABUPATEN OGAN KOMERING ILIR (Program Studi Ilmu Kesehatan STIKES Abdi Nusa Pangkalpinang, 2022)
Uric acid is the end product of purine metabolism, which is a component of nucleic acid found in the nucleus of body cells. Gout can occur due toage, gender, excessive intake of purine compounds, excessive alcohol consumption and physical activity. The purpose of the study was todetermine what factors cause gout.method cross-selection The examination method uses the POCT (Point of Care Testing) method. Based onthe results of the study for the male category as much as 33.4% is not normal, while for the female category as much as 38.1% is not normal, forthe obese category as much as 29.6% while for the normal category as much as 55.5 % and 14.8% for the thin category.